Environmental change and globalization double exposures - Leichenko, Robin M.; O'Brien, Karen L. (New York ; Oxford : Oxford University Press, 2008)
This work explores the connections between two of the most transformative processes of the 21st century, global environmental change and globalization. It presents a conceptual framework for analyzing the interactions between these two processes.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Global environmental change; Globalization